Narrativas autobiográficas com estudantes do fundamental II: percepção das Políticas Públicas - Pessoa, Jocélia Maria Santos de Lira (2023)
In Brazil, the right to schooling is guaranteed by law. Schools have advanced in teaching methodologies and practices, aiming to promote comprehensive education. However, they exhibit flaws when failing to fully and effectively fulfill their role in student development, creating room for segregation and evasion. Society expects and demands that schools address social and historical issues where public policies fall short, yet there is a lack of questioning and demand for critical, political, and quality education. With this in mind, this research sought to understand how adolescents, through their narratives and interpretations, perceive their schooling process influenced by public policies. The study adopted a qualitative approach, and autobiographical narratives were used as the data collection method to facilitate interactivity and critical reflection. The sample consisted of 10 teenagers in the 9th grade at a full-time public school in Sobral. The narratives brought to light various public policies impacting education both directly and indirectly, such as full-time schooling, school kits, income distribution programs, and school meals. Additionally, themes emerged that influence the educational process without being a public policy. The findings indicate an awareness of public policies among these teenagers, alongside a need for platforms for discussion and expression. The results of this paper will also be shared at a technical event with professionals involved in public policy development in the area of the school, aiming to enhance public policies targeted at children and adolescents.